Development of a model for fibroblast-led collective migration from breast cancer cell spheroids to study radiation effects on invasiveness - Mei, Jia; Boehland, Claudia; Geiger, Anika; Baur, Iris; Berner, Kristina; Heuer, Steffen; Liu, Xue; Mataite, Laura; Melo-Narvaez, M. Camila; Oezkaya, Erdem; Rupp, Anna; Siebenwirth, Christian; et al. (Radiation Oncology, 2021)
Background: Invasiveness is a major factor contributing to metastasis of tumour cells. Given the broad variety and plasticity of invasion mechanisms, assessing potential metastasis-promoting effects of irradiation for specific mechanisms is important for further understanding of potential adverse effects of radiotherapy. In fibroblast-led invasion mechanisms, fibroblasts produce tracks in the extracellular matrix in which cancer cells with epithelial traits can follow. So far, the influence of irradiation on this type of invasion mechanisms has not been assessed. Methods: By matrix-embedding coculture spheroids consisting of breast cancer cells (MCF-7, BT474) and normal fibroblasts, we established a model for fibroblast-led invasion. To demonstrate applicability of this model, spheroid growth and invasion behaviour after irradiation with 5 Gy were investigated by microscopy and image analysis. Results: When not embedded, irradiation caused a significant growth delay in the spheroids. When irradiating the spheroids with 5 Gy before embedding, we find comparable maximum migration distance in fibroblast monoculture and in coculture samples as seen in unirradiated samples. Depending on the fibroblast strain, the number of invading cells remained constant or was reduced. Conclusion: In this spheroid model and with the cell lines and fibroblast strains used, irradiation does not have a major invasion-promoting effect. 3D analysis of invasiveness allows to uncouple effects on invading cell number and maximum invasion distance when assessing radiation effects.
CRIS-Team Scopus Importer:2023-04-20